Efficiency and features of projects: factcheck.kz and stopfake.kz in Kazakh journalism (Herald of Journalism, 2023)
The article is devoted to comparing and evaluating the work and peculiarities of the factcheck.kz and stopfake.kz projects in today's Kazakh journalism.Fact checking determines whether any cultural-scientific information or small news are true or false. In other countries, fact-checking resources have their own features and directions, and the opinions of experts are different. The struggle with false information, how Kazakhstan and the countries of the world are responding to this problem in the face of its danger is relevant in today's public communication field.The purpose of the research article is to show the effectiveness and specificity of fact-checking resources, the main mechanism of combating false information in the modern world media environment, to verify information transmitted at a very large speed under the influence of the intensity of the flow of information and digital technologies.During the writing of the article, fact-checking work was analyzed, and its history and development features were summarized. A comparative analysis of the methods of data verification abroad was carried out.False information has entered our lives so quickly that it has become difficult to distinguish false from true information.Misunderstandings in various situations may occur if people cannot distinguish false from true information, so the necessity and importance of the factcheck.kz and stopfake.kz projects can be summarized. Evaluating the effectiveness and use of the factcheck.kz and stopfake.kz projects in information differentiation will open the way for fundamental scientific research in this direction.         Keywords: journalism, factchek.kz, stopfake.kz, project, fact-checking, false information, foreign country, efficiency.